Równania Asymptotyczne i Efekt Brzegowy dla Płyt o Złożonej Strukturze - Konieczny, S. (Engineering Transactions, 1971)
The equations describing grid plates with a complex structure contain a small parameter which occurs at the differential operator of the highest order in the set of displacement equations. This makes it possible to obtain the approximate solution using the asymptotic approach. In the paper is given a set of equations for the asymptotic theory, together with the equation for the boundary effect. An equation of the fourth order is obtained for the asymptotic theory, and of the second order for the boundary effect. The order of the set of equations is unchanged - being still six - and thereby we can exactly satisfy the three boundary conditions.